MENGGALI KEARIFAN LOKAL DALAM MEMBENTUK KEPEMIMPINAN KRISTEN KONTEKSTUAL - Limbong Hermin; Elsa Sibidang (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
This article discusses the importance of contextualization in the formation of Christian leadership in the midst of a multicultural and pluralistic Indonesian society. This study uses a qualitative approach with a literature study method, which aims to explore the integration between local wisdom values and Christian leadership principles derived from the Holy Bible. Through a study of cultural values such as mutual cooperation, deliberation, respect for others, and devotion to the community, it was found that local Indonesian culture contains many elements that are in line with the values of the Gospel. This article identifies four main aspects in the formation of contextual Christian leadership, namely: integration of local values and principles of faith, inclusive leadership models amidst plurality, the role of theological education and the church in formation, and the challenges and risks of contextualization. Although there are many benefits offered, the contextualization process also faces various challenges such as the potential for syncretism, internal church resistance, cultural bias, and limited literature. Therefore, a reflective and responsible approach is needed so that contextualization truly produces Christian leaders who are relevant, transformative, and remain faithful to the truth of the Gospel. This article is expected to provide theoretical and practical contributions to the development of Christian leadership in Indonesia that is based on the richness of local culture